Adequacy of Parent-Packed Lunches and Preschooler's Consumption Compared to Dietary Reference Intake Recommendations. (3rd April 2017) - Romo-Palafox, Maria Jose; Ranjit, Nalini; Sweitzer, Sara J.; Roberts-Gray, Cindy; Byrd-Williams, Courtney E.; Briley, Margaret E.; Hoelscher, Deanna M.
Abstract: Background : U.S. preschool children consume inadequate amounts of key nutrients. Understanding the contents of lunches packed by parents and consumed by their children can help identify areas of opportunity for the development of healthy food preferences. Objective : To evaluate the nutrient adequacy of lunches packed by parents and consumed by children attending early care and education (ECE) centers. Methods : Baseline data from 607 parent–child dyads in the "Lunch Is in the Bag" cluster-randomized controlled trial in Central Texas were examined. Foods packed by parents and consumed by children in sack lunches were observed at 30 ECE centers on 2 nonconsecutive days. Mean levels of energy, macronutrients, vitamins, and minerals were estimated with covariate-adjusted multilevel regression models that accounted for center-level clustering and repeated within-child measures. Results : Energy (kilocalories) was 602.48 for packed lunches compared to 374.40 for consumed lunches. In packed lunches, percentage of energy as macronutrients for protein (14.8%), carbohydrate (55.9%), and total fat (31.2%) were within the acceptable macronutrient distribution range (AMDR) for the children's ages. Sugar (28.9% of energy) was above the AMDR recommendation. Only a quarter of parents packed 33% or more of the child's dietary reference intake (DRI) for dietary fiber. Over half the parents packed 33% or more of the DRI for vitamin A and calcium, and less than one in 8 packed 33% of the DRI for potassium. Children consistently consumed between 60 and 80% of the nutrients that were packed. Conclusions : Preschool children rely on parents to present them with healthy food choices, but lunches packed by parents for their preschool children do not consistently provide adequate nutrients. These data and the relationships between the dietary quality of packed and consumed lunches can be useful information to guide nutrition behavior change through targeted interventions.